The Controversy Continues Again: which Direct Anticoagulant is More Effective and Safe when Administered to Patients with Atrial Fibrillation? - S. Yu. Martsevich (Рациональная фармакотерапия в кардиологии)
The data from the observational study of M. Fralick et al. were analyzed in the article. The authors analyzed a large database of patients with atrial fibrillation and concluded that rivaroxaban is inferior to apixaban in its ability to prevent ischemic stroke and systemic embolism and is more likely to cause bleeding. Serious methodological defects of the analysis take place. No statistical methods are capable of correcting the absence of such important information in the database as the doctor's motives for prescribing a particular drug, as well as the patient's adherence to taking it. It is also noted that the patients included in the study, according to clinical characteristics, did not correspond to the typical population of patients with atrial fibrillation. The author considers the conclusions made in the mentioned work to be unauthorized.